2010
DOI: 10.1007/s10815-010-9510-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of progesterone receptor polymorphism with idiopathic recurrent pregnancy loss in Taiwanese Han population

Abstract: Purpose Recurrent pregnancy loss (RPL) could be caused by insufficient progesterone in the luteal phase of menstruation and early pregnancy. Progesterone plays a critical role in oocyte maturation, embryo implantation and placenta maintenance in early gestation. This study was set out to investigate the association between polymorphisms of the progesterone receptor (PGR) gene and idiopathic RPL. Methods One hundred twenty-one women with a history of idiopathic recurrent pregnancy loss (RPL) and 179 control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
4
29
0
4
Order By: Relevance
“…Previous studies have demonstrated that the presence of *2 allele in the mother is associated with recurrent abortions, implantation failure and pre-term births [34,39]. While there are reports that have refuted these findings [5,23], the influence of maternal genome on embryonic growth cannot be underestimated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have demonstrated that the presence of *2 allele in the mother is associated with recurrent abortions, implantation failure and pre-term births [34,39]. While there are reports that have refuted these findings [5,23], the influence of maternal genome on embryonic growth cannot be underestimated.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, the PROGINS variant displays decreased transactivation activity, the resulting protein has poor bioactivity and affects cell cycle in cultured endometrial cells [11,33]. Intriguingly, studies have demonstrated that the presence of this polymorphism increases the risk of women towards gynecologic disorders including cancers [30,32,34,39]. Thus, we hypothesized that such genetic variation in the PR gene may reduce PR mRNA/protein expression in the testis leading to male factor infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Рецепторна відповідь на прогестерон може залежати від однонуклеотидного полімор-фізму (SNP) PGR [11,12]. Станом на 2016 р. описано 5732 поліморфізмів PGR, проте за останні роки було проведено лише декілька досліджень, які вказують на роль SNPs PGR у формуванні схильності до виникнення звичного невиношування вагітності [11][12][13][14][15][16]. SNPs PGR може спричиняти порушення експресії PGR, тим самим змінюючи перебіг біохімічних процесів в організмі жінки і сприяючи розвитку патологічного процесу та/або впливати на перебіг останнього [12].…”
Section: вступunclassified
“…Загалом, це дослідження показало наявність зв'язку між SNPs PGR та звичним невиношуванням вагітності [15]. У цьому ж році інші дослідники показали, що у когорті латиноамериканців та європеоїдів rs500760 може впливати на ефективність прогестеро-нової терапії для попередження передчасних пологів у терміні гестації до 37 тиж [11].…”
Section: вступunclassified
See 1 more Smart Citation